Religiosity, stress, and depressive symptoms among nursing and medical students during the middle stage of the COVID-19 pandemic: A cross-sectional study in Morocco - Rammouz, Ismail; Lahlou, Laila; Salehddine, Zineb; Eloumary, Omar; Laaraj, Hicham; Ouhamou, Mina; Mouhadi, Khalid; Doufik, Jalal; Aalouane, Rachid; Boujraf, Said (Frontiers in Psychiatry, 2023)
Background Recent studies on nursing and medical students showed a higher prevalence of depression and stress than the general population. Religiosity and spirituality are common in Muslim countries and are usually used as a means of coping strategy for psychological and mental disorders. Objective Our objective was to evaluate the association between religious actions, depressive symptoms, and stress among students of nursing education lasting 3 years and students from the first 3 years of medical education lasting 7 years. The study was conducted at Ibn Zohr University of Agadir, Morocco. Method A sample of different stages of nursing and medical students was recruited. Religiosity was assessed by Muslim Belief into Action (M.BIAC) scale. The depressive symptoms and stress were, respectively, assessed by the Beck Depression Inventory (BDI-II) and Perceived Stress Scale (PSS). Results Four hundred and thirteen students participated in this study. Our results showed a high prevalence of depressive symptoms (62.2%) and stress (66.8%). The depression scores were higher in the following subsample categories: students in the first 2 years of studies, female medical students, and nursing students with significant differences. The recorded religiosity was greater among students without depression compared to students with depression (p < 0.001). In the multivariate regression, the BIAC score demonstrated religiosity as neither a risk factor nor a protective factor of depression. Conclusion Religiosity constitutes a protective factor of depression and stress among nursing and medical students. This should improve the student's ability to cope with stressful situations during their training. Prospective studies are needed to further investigate this association and how religiosity improves mental health. This would contribute to improved academic performance and wellbeing among medical and nursing students.